TEMPORAL VARIATION OF THE WATER QUALITY OF A PERMANENT WATERCOURSE: CASE OUED BOUSSELAM - M., . Dehbi*1, . Messai-Maane2, S., . Sekki3 A. (university of eloued جامعة الوادي, 2020)
In order to assess the degree of pollution of surface water from Boussalem river from the city of Setif, we conducted during 2014; a study of physical and chemical characteristics of surface water. The results showed that water is loaded into mineral matter in terms of electrical conductivity (Avg = 1059,18 μS/cm ± 631,7), in turbidity (Avg = 15,713 NTU ± 22,19), in TSS (Avg = 189 mg/l ± 119,5), with low dissolved oxygen (Avg = 2,98 mg/l ± 2 ,44). The pH is closed to neutrality (Avg = 7,78 ± 0,74), the temperature is 17°C ± 11,13). Also, one revealed according to the results which water of Bousselam river is bad according to the quality standards of surface water and this is directly related to factors anthropic.
artical
Keywords: Surface water; Pollution; Physicochemical parameters; Boussellam river; Setif.